2020
DOI: 10.1088/1742-6596/1641/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Impact of M-banking on Individual Performance of the DeLone & McLean Method and TTF Perpective

Abstract: Currently the public has a curiosity about e-commerce applications that are growing rapidly, such as Mobile banking (m-banking). The development of m-banking can be seen from user satisfaction, end-user interest and the success of everyone using m-banking. This study adds the Task Technology Fit (TTF) model to the DeLone & McLean model for the purpose of knowing the success of individuals using m-banking. We used 102 respondents to answer all the questions in the questionnaire. The results show that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
2
1
0
1
Order By: Relevance
“…This implies that, in general, performance expectancy is an essential driver of user satisfaction. These results concur with those of previous research in which performance expectancy was found to be an important antecedent of m-banking satisfaction (Azizah et al. , 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that, in general, performance expectancy is an essential driver of user satisfaction. These results concur with those of previous research in which performance expectancy was found to be an important antecedent of m-banking satisfaction (Azizah et al. , 2020).…”
Section: Resultssupporting
confidence: 93%
“…This implies that, in general, performance expectancy is an essential driver of user satisfaction. These results concur with those of previous research in which performance expectancy was found to be an important antecedent of m-banking satisfaction (Azizah et al, 2020). This indicates that users are inclined to adopt mobile banking when they perceive it as beneficial for their banking needs (Jadil et al, 2021).…”
Section: Main Effects and Heterogeneitysupporting
confidence: 91%
“…Pengukuran variabel penelitian Webqual 4.0 diadaptasi dari penelitian sebelumnya dengan menggunakan tiga dimensi yaitu usability quality, information quality, dan service interaction quality [3]. Pengukuran variabel kepuasan diadaptasi dari model DeLone & McLean [12]. Sedangkan pengukuran continuance intention diadaptasi dari penelitian Rahi et al [10].…”
Section: Pendahuluanunclassified
“…The results stated that service quality and information quality greatly influence a person in adopting a technology, and system quality has no effect in the context of FinTech. Meanwhile, Azizah et al (2020) found that system quality had no significant effect on satisfaction. This result contradicted with several studies which stated that system quality has a significant effect on the adoption of mobile banking applications in Saudi Arabia (Baabdullah et al, 2019) and e-learning in Nigeria (Yakubu & Dasuki, 2018).…”
Section: Introductionmentioning
confidence: 99%